2017
DOI: 10.1186/s10194-017-0774-6
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic headache in patients with minimal traumatic intracranial hemorrhage after traumatic brain injury: a retrospective matched case-control study

Abstract: BackgroundNo evidence is available on the risks of neurologically asymptomatic minimal traumatic intracranial hemorrhage (mTIH) in patients with traumatic brain injury (TBI) for post-traumatic headache (PTH). The purpose of this study was to investigate whether mTIH in patients with TBI was associated with PTH and to evaluate its risk factors.MethodsBetween September 2009 and December 2014, 1484 patients with TBI were treated at our institution, 57 of whom had mTIH after TBI and were include in this study. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…In both cases, the presence of PTSD may play a relevant role in disability and psychosocial impairment related to PPTH. The current literature upon this topic is growing rapidly, showing a spreading interest in this area in terms of diagnostic tool applications, differential diagnosis among headaches, and epidemiological data from emergency and psychiatric departments, which are the ideal frame for unbiased studies on these patients, in order to have more valid data in the future that will help us understand if this research path is worth pursuing [65][66][67][68][69][70][71]. Importantly, we have also to carefully address the link between emotional turmoil, which is closely linked to suicidal behavior, in PTH patients.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, the presence of PTSD may play a relevant role in disability and psychosocial impairment related to PPTH. The current literature upon this topic is growing rapidly, showing a spreading interest in this area in terms of diagnostic tool applications, differential diagnosis among headaches, and epidemiological data from emergency and psychiatric departments, which are the ideal frame for unbiased studies on these patients, in order to have more valid data in the future that will help us understand if this research path is worth pursuing [65][66][67][68][69][70][71]. Importantly, we have also to carefully address the link between emotional turmoil, which is closely linked to suicidal behavior, in PTH patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent study from Korea, the authors found that HAIH occurred more frequently 12 months post-injury in patients with minimal traumatic intracranial hemorrhage after MTBI than in those without. 29 Research on imaging findings as a predictor for headache is scarce, but some studies have investigated imaging findings as a predictor for post-concussive symptoms (PCS), a cluster of post-traumatic symptoms, including headache. A prospective study from Finland found no significant differences in the rates of PCS 1 month and 1 year following MTBI, in participants with or without MRI abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, this might lead to another clinical problem. Intracranial hemorrhage is associated with increased incidence of postconcussion syndrome and postconcussion headache [39,40]. Treatment is available for these patients, but if they are not identified by emergency head CT, another means of identifying them is necessary so they can be offered treatment [41,42].…”
Section: Discussionmentioning
confidence: 99%